2012
DOI: 10.1007/s13193-012-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Margins on Disease Free Survival Following Hepatic Resection for Colorectal Metastasis: A Meta-Analysis

Abstract: The aim of our study was to conduct a metaanalysis of reports published on hepatic resection for colorectal liver metastases (CRLM) and determine if a negative margin ≥1 cm confers a disease free survival (DFS) advantage over sub-centimeter negative margins. The 357 initially selected articles were screened to identify 90 articles of interest of which eleven were finally included in the metaanalysis. Patients with positive margins were excluded from the meta-analysis. Meta-analysis was performed using STATA 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The last decade has seen an increasingly aggressive approach to management of CRLM, often with the intention to cure 3 . Nevertheless, the recurrence rate after curative intent treatment for CRLM remains high, with nearly 50% recurring within 2 years 4‐6 and a 5‐year disease‐free survival of only 27.9% 7 . Most CRLM surveillance programs involve frequent computed tomographic (CT) scans 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The last decade has seen an increasingly aggressive approach to management of CRLM, often with the intention to cure 3 . Nevertheless, the recurrence rate after curative intent treatment for CRLM remains high, with nearly 50% recurring within 2 years 4‐6 and a 5‐year disease‐free survival of only 27.9% 7 . Most CRLM surveillance programs involve frequent computed tomographic (CT) scans 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, resection margins were classified as clear where there was a negative margin of at least 10 mm, as this has been shown to confer a survival benefit. [2][3][4][5] However, recent studies reported similar survival outcomes in patients with margins of 1-9 mm, compared to 10 mm margin resections (5-year OS rates after 10 mm and <10 mm resection of 57% and 61%, respectively). [6][7][8] This was supported by the results of large international, multi-centre retrospective study, where patients were stratified into those with positive margins, and those with negative margins of either 1-4 mm, 5-9 mm, or >10 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant advances in local and systematic therapy, colorectal cancer remains one of the top leading causes of cancer‐related deaths worldwide 1–3 . Survival rates decline significantly with metastatic disease, where the most common location of spread is to the liver 1,4,5 . In the setting of oligometastatic disease, selected patients can undergo resection of the primary and metastastatic disease with curative intent, resulting in favorable 5‐year overall survival (OS) rates from 40% to 60% 4,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Survival rates decline significantly with metastatic disease, where the most common location of spread is to the liver 1,4,5 . In the setting of oligometastatic disease, selected patients can undergo resection of the primary and metastastatic disease with curative intent, resulting in favorable 5‐year overall survival (OS) rates from 40% to 60% 4,6,7 . However, for the significant proportion of patients who experience subsequent recurrence (i.e., following their initial liver resection), there lacks robust evidence to guide management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation